SITUS INVERSUS TOTALIS IN NEWBORN: A CASE REPORT - Stomnaroska, Orhideja; Jancevska, Aleksandra; Ristovska, Sanja (Journal of Morphological Sciences, 2024)
Situs inversus totalis (SIT) is a rare congenital abnormality and a complex disorder of embryological morphogenesis. It is characterized by a mirror-image transposition of the abdominal and the thoracic organs. Frequently it is associated with other congenital anomalies, congenital heart malformations being found in 3-9% of patients with SIT. Isolated SIT is also reported. We report a preterm newborn treated with non-invasive ventilation (CPAP) for respiratory distress. The X-ray of the lungs revealed the expected respiratory distress syndrome (RDS), but surprisingly and accidentally dextrocardia and left sided liver. Heart ultrasound showed dextrocardia without congenital anomaly. Abdominal ultrasound confirmed left-sided liver, and right sided spleen. After a lengthy 30 days stay the baby was discharged at home without any complication. SIT is an extraordinary rare condition in neonates. Timely diagnosis in-utero is important for prenatal and postnatal monitoring of newborns. Most of the patients with SIT without congenital anomalies do not have any complications in their life. However, appropriate information about the condition is important to prevent complications during some invasive and surgical interventions. Kewwords: situs inversus totalis, newborn.